Project management system on piling project (bored-cast-in-place pile) - Ng, Lay Hua. (2009)
The aim of this report is to evaluate the effectiveness of a project management system currently adopted by a local piling company. The scope encompasses the identification of common problems associated with a piling project. The project management system shown in the form of a flow chart is discussed and an application of the system in a completed project is studied. The major process of the bored pile installation is translated into a flow diagram using Powersim Software and each variable used is formulated. The model is simulated for 100 times and a simulated construction period is obtained. A sensitivity analysis of the model is also carried out on the allocation of resources.